Determination and Prediction of Some Soil Properties using Partial Least Square (PLS) Calibration and Mid-Infra Red (MIR) Spectroscopy Analysis - Djuuna, Irnanda Aiko Fifi; Abbott, Lynette; Russell, Craig (JOURNAL OF TROPICAL SOILS, 2011)
Soil chemical, physical and biological analyses are a crucial but often expensive and time-consuming step in the characterization of soils. Rapid and accurate predictions and relatively simple methods are ideally needed for soil analysis. The objective of this study was to predict some soil properties (e.g. pH, EC, total C, total N,C/N, NH4-N, NO3-N, P, K, clay, silt, and sand and soil microbial biomass carbon) across the Wickepin farm during summer season using a Mid-Infra Red - Partial Least Square (MIR–PLS) method. The 291 soil samples were analyzed bothwith soil extraction procedure and MIR Spectrometer. Calibrations were developed between MIR spectral data and the results of soil extraction procedures. Results using the PLS-MIR showed that MIR-predicted values were almost as highly correlated to the measured value obtained by the soil extraction method of total carbon, total nitrogen and soil pH. Values for EC, NH4-N, NO3-N, C/N, P, K, clay, silt, sand, and soil microbial biomass carbon were not successfully predicted by the MIR – PLS technique. There was a tendency for these factors to correlate with the MIR predicted value, but the correlation values were very low. This study has confirmed that the MIR-PLS method can be used to predict some soil properties based on calibrations of MIR values.Keywords: MIR-Partial Least Square, MIR-Spectroscopy, soil properties